The Integration of Digital Technology in Islamic Religious Education Learning and Administration at SMP Negeri 2 Baturraden - Faoji Mansur; Muh Hanif (Teknologi Pendidikan ID, 2026)
This study aims to examine the utilization of digital technology in Islamic Religious Education (IRE) learning and administration at SMP Negeri 2 Baturraden. The study employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving Islamic Religious Education teachers as the research informants. The findings reveal that SMP Negeri 2 Baturraden has integrated digital technology into both learning activities and school administration. In the learning process, teachers utilize various digital media, such as YouTube, PowerPoint, Canva, Kahoot, and Quizizz, to enhance student engagement and learning motivation. The use of digital media enables students to become more actively involved and facilitates a better understanding of the learning materials. In terms of administration, the school employs digital technologies, including cloud-based storage services for document management, mobile and facial recognition-based attendance systems, as well as computer laboratories and internet access facilities. The implementation of digital technology has a positive impact on the effectiveness of teaching and administrative management, although several challenges remain, such as monitoring students' device usage and validating the authenticity of digitally based learning outcomes. Overall, the use of digital technology supports a more innovative, efficient, and interactive learning environment.